Tumor-Associated Macrophages Regulate PD-1/PD-L1 Immunosuppression - Pu, Yunzhou; Ji, Qing (Frontiers in Immunology, 2022)
Anti-programmed cell death 1 (PD-1) or anti-PD-ligand (L) 1 drugs, as classic immune checkpoint inhibitors, are considered promising treatment strategies for tumors. In clinical practice, some cancer patients experience drug resistance and disease progression in the process of anti-PD-1/PD-L1 immunotherapy. Tumor-associated macrophages (TAMs) play key roles in regulating PD-1/PD-L1 immunosuppression by inhibiting the recruitment and function of T cells through cytokines, superficial immune checkpoint ligands and exosomes. There are several therapies available to recover the anticancer efficacy of PD-1/PD-L1 inhibitors by targeting TAMs, including the inhibition of TAM differentiation and re-education of TAM activation. In this review, we will summarize the roles and mechanisms of TAMs in PD-1/PD-L1 blocker resistance. Furthermore, we will discuss the therapies that were designed to deplete TAMs, re-educate TAMs, and intervene with chemokines secreted by TAMs and exosomes from M1 macrophages, providing more potential options to improve the efficacy of PD-1/PD-L1 inhibitors.